Extended-Spectrum Beta-Lactamase (ESBL) Producing, Multidrug-Resistant (MDR) Uropathogens and Their Antimicrobial Susceptibility Profile: A Tertiary Care Hospital Experience: Bacterial Uropathogens - Farooq, Muhammad; Gul, Ambreen; Mahmood, Asad; Anwar, Muhammad; Mir, Tahreen Salima; Altaf, Ahsan (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine extended-spectrum beta-lactamase (ESBL) producing, multidrug-resistant (MDR) uropathogens and their antimicrobial susceptibility profile in various age groups and gender.Study Design: Comparative cross sectional study.Place and Duration of Study: Department of Pathology, Combined Military Hospital Abbottabad, from Jan to Dec 2018.Methodology: A total of 727 urine samples were collected and inoculated on cysteine lactose electrolyte deficient (CLED) agar plates (Oxoid). Plates were incubated for 24-48 hours at 37°C ±2 aerobically. Growth was identified by standard techniques. Antimicrobial susceptibility was determined.Results: The rate of positive culture was 19%. Uropathogens spectrum showed that there were Escherichia coli 82 (59.85%), Klebsiella pneumoniae 37 (27.01%), Serratia spp. 4 (2.92%), Enterobacter spp. 4 (2.92%), Citrobacter spp. 3 (2.19%), Pseudomonas aeruginosa 2 (1.46%), Staphylococcus saprophyticus 3 (2.19%) and Enterococcus spp. 2 (1.46%). Susceptibility was as follows: Ampicillin (2.92%), Co-amoxiclav (26.28%), Ceftriaxone (64.69%), Cefepime (58.39%), Tazobactum-piperacillin (63.50%), Imipenem (82 %), Ciprofloxacin (27.01%), Co-trimoxazole (29.93%), Amikacin (74.45%), Nitrofurantoin (81.75%) and SulbactumCefoperazone (54.48%). Among 130 Gram negative bacilli (GNB) from urinary isolates 71(54.6%) were ESBL producer and 59 (44.3%) were non-ESBL producers. No isolate of Serratia spp, Enterobacter spp. and Citrobacter spp. Were producing ESBL. Out of130, Gram negative bacilli 92 (70.8%) were MDR and 38 (29.2%) were non-MDR.Conclusion: Extended-spectrum beta-lactamase production and MDR is significantly high in uropathogens. Empirical treatment followed by a de-escalation of antimicrobial is suggested after culture report in order to combat the problem of emerging antibiotic resistance.Keywords: ,